Da impossibilidade de liquidação da garantia fidejussória ofertada pelo contribuinte antes do trânsito em julgado dos embargos à execução fiscal - Santos, Enzo Meireles (2023)
The present work aims to demonstrate, from the perspective of Law No. 6.830/80 and the principles that support it, the absence of legal reasons justifying the enforcement of sureties offered by taxpayers before the final decision on the corresponding tax execution appeals. To achieve this, the following was compiled: 1) the legislation applicable to tax credit guarantees, especially those provided by third parties (bank guarantees and insurance bonds); 2) the main arguments used by the tax authorities to support the viability of the early liquidation request of sureties provided by third parties and the reasons why it is believed that they should not be accepted by the Courts; 3) judicial decisions issued by various Courts on the subject. Finally, it was noted what harm the continuous acceptance of this thesis will have on taxpayers who wish to dispute the validity of a tax credit deemed undue, as well as the necessity of instruments that preserve the surety until the final decision on the execution appeals.